Web-Based Neighborhood Management Information System Using Laravel PHP Framework (Case Study RT. 07 Manggung, Wukirsari, Imogiri, Bantul) - Setiawan, Johan; Rahman, Arif; Sugiantoro, Bambang (Proceeding International Conference on Science and Engineering, 2020)
Management and management of data is one of the most important things for neighbor administrators, so data and information related to the notulency, attendance, financial and assets must be accessed quickly and precisely. RT 07 Hamlet Manggung is the government line that is closest to the Community. Currently the recording of data for Notulency, attendance, family cards and assets is still Manual and has not used any technology that improves effectiveness in data management pillars Neighbors. This system is built using Unified Software Development development method process (USDP), with the Unified Modelling Language (UML) modelling. In the inception phase all RT management data related to system requirements, elaboration phase is done to expand management system concept that already formed in phase inception, phase contruction done making management system, and in the transition phase is done to expand the system. Management. This maturation needs to be done to analyse whether the information system that has been made according to user needs. Then the system is built with the language PHP programming and MySQL databases using the Laravel framework, once it is done test system using alpha test and beta test.